ON FULLY STABLE ACTS - Abbas, Mehdi Sadiq; Baanoon, Hiba Rabee (Italian Journal of Pure and Applied Mathematics, 2015)
The purpose of this paper is to introduce and investigate the fully stable acts as a concept generalizing fully stable modules but is stronger than that of duo acts. In this study, we consider some properties and characterizations of the class of fully stable acts, and the relations between this class and other well studied classes of acts, like quasi-injective acts and acts satisfying Baer's criterion.